PENGARUH PEMBERIAN IKAN HIAS JANTAN TERHADAP JUMLAH LARVA AEDES AEGYPTI TAHUN 2015 - Apriliyah Joshua; Koerniasari .; Demes Nurmayanti (GEMA LINGKUNGAN KESEHATAN, 2015)
Dengue Hemorrhagic Fever (DHF) becomes a public health problem In Indonesia due to high number of sufferers and its wide spread. Control methods have been carried out chemically and non-chemically. Use of mosquitofish is one of the biological controls in which certain types of fish used as natural enemies or predators of mosquito larvae. The purpose of this study is todetermine effect of male ornamental aquarium fish to the number of Aedes aegypti larvae. This is a quasi-experimental research carried out by conducting experiment on Betta crown tail fish and Pterophyllum altum eting ability to the number of Aedes aegypti larvae. Data used in this research is primary and secondary data.  The primary data were obtained fromobservation during experiment of the number of Aedes aegypti larvae eaten by both types ofornamental fish, while the secondary data was data from books and journals supporting the research.Result showed that Betta crown tail fish were the most influencing fish with an average eating ability of 282 larvae per day. While average of Pterophylum Altum eating ability was 248larvae per day. Result of the research lead to suggestion on the use of Betta crown tail fish as predators of Aedes aegypti larvae in and medium size bath up and Pterophylum Altum fish for the tub large size one.